2017
DOI: 10.3847/1538-4357/aa82b5
|View full text |Cite
|
Sign up to set email alerts
|

Growth of First Galaxies: Impacts of Star Formation and Stellar Feedback

Abstract: Recent observations have detected galaxies at high-redshift z ∼ 6 − 11, and revealed the diversity of their physical properties, from normal star-forming galaxies to starburst galaxies. To understand the properties of these observed galaxies, it is crucial to understand the star formation (SF) history of high-redshift galaxies under the influence of stellar feedback. In this work, we present the results of cosmological hydrodynamic simulations with zoom-in initial conditions, and investigate the formation of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 96 publications
(148 reference statements)
1
33
0
Order By: Relevance
“…These studies reveal that stellar and supernova (SN) feedback are crucial for galaxy evolution. In particular, Yajima et al (2017a) studied galaxy evolution in massive halos (M h 10 11 M ) at z 6 using cosmological hydrodynamic simulations, and found that the star formation occurs intermittently due to SN feedback and gas accretion (see also, Kimm & Cen 2014). However, the radiative properties associated with the bursty star-formation history are not fully understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…These studies reveal that stellar and supernova (SN) feedback are crucial for galaxy evolution. In particular, Yajima et al (2017a) studied galaxy evolution in massive halos (M h 10 11 M ) at z 6 using cosmological hydrodynamic simulations, and found that the star formation occurs intermittently due to SN feedback and gas accretion (see also, Kimm & Cen 2014). However, the radiative properties associated with the bursty star-formation history are not fully understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…The focus has instead been on theoretical studies to investigate how the first galaxies were assembled, and how the first generation of stars played a role in shaping the conditions for their formation (e.g. Maio et al 2010;Wise et al 2012;Johnson et al 2013;Xu et al 2016;Yajima et al 2017;Kimm et al 2017;Wilkins et al 2017;Griffen et al 2018;Ma et al 2018;Jaacks et al 2018a). Owing to their small size (r vir = 1 − 3 kpc) and rather short evolutionary timescales (<1 Gyr), the first galaxies are an ideal target for numerical studies, allowing simulators, in principle, to build up a galaxy in an ab-initio fashion.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Susa & Umemura (2004) showed that the morphology of galaxies could change significantly in different UV background fields due to the suppression of star formation. Okamoto et al (2008) indi- cated that the UV background could reduce the cosmic star formation history significantly because of the suppression of star formation in dwarf galaxies (see also, Hasegawa & Semelin 2013;Yajima et al 2017). These previous works focused on the photo-evaporation effects of gas by the Lymancontinuum photons.…”
Section: Impact Of Hydrogen Moleculesmentioning
confidence: 99%
“…Note that the high resolution with < 1 pc is required to follow the cloud formation via thermal instability as we discuss in the Appendix. Current cosmological simulations are still difficult to resolve such small scales (e.g., Kim et al 2017;Yajima et al 2017). In addition, the massive clouds could form within several Myr, while the mass inflow to the galactic center occurs over the galaxy dynamical time > 10 Myr.…”
Section: Formation Of Cold Gas Clouds Withmentioning
confidence: 99%
See 1 more Smart Citation